Heterogeneity of airways mucus: variations in the amounts and glycoforms of the major oligomeric mucins MUC5AC and MUC5B - Kirkham, Sara; Sheehan, John K; Knight, David; Richardson, Paul S; Thornton, David J (Biochemical journal, 2002)
Respiratory mucus contains a mixture of gel-forming mucins but the functional significance of these different mucin species is unknown. To help gain a better understanding of mucus in airways we therefore need to ascertain the concentration of each of the gel-forming mucins within respiratory secretions. Thus the aim of this study was to determine the amounts of specific gel-forming mucins directly from solubilized secretions of the airways and purified mucin preparations. We investigated the feasibility of using direct-binding ELISA employing mucin-specific antisera but were unable to obtain reliable data owing to interference with the immobilization of the mucins on the assay surface by 6 M urea and high levels of non-mucin proteins. We therefore developed an alternative approach based on quantitative Western blotting after agarose-gel electrophoresis, which was not subject to these problems. Here we demonstrate that this procedure provides reliable and reproducible data and have employed it to determine the amounts of the MUC2, MUC5AC and MUC5B mucins in saline-induced sputa from healthy airways and spontaneous sputa from asthmatic airways. Additionally we have used this procedure to analyse these glycoproteins in mucin preparations purified from cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD) mucus. Our findings indicate that MUC5AC and MUC5B are the major oligomeric mucins and that airways mucus contains variable amounts of these glycoproteins. By contrast, the MUC2 mucin comprised, at most, only 2.5% of the weight of the gel-forming mucins, indicating that MUC2 is a minor component in sputum. Finally, we show that the amounts and glycosylated variants of the MUC5AC and MUC5B mucins can be altered significantly in diseased airways with, for instance, an increase in the low-charge form of the MUC5B mucin in CF and COPD mucus.